2018
DOI: 10.1107/s2053230x17017708
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a novel monotreme-specific protein with antimicrobial activity from the milk of the platypus

Abstract: Monotreme lactation protein (MLP) is a recently identified protein with antimicrobial activity. It is present in the milk of monotremes and is unique to this lineage. To characterize MLP and to gain insight into the potential role of this protein in the evolution of lactation, the crystal structure of duck-billed platypus (Ornithorhynchus anatinus) MLP was determined at 1.82 Å resolution. This is the first structure to be reported for this novel, mammalian antibacterial protein. MLP was expressed as a FLAG epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…platypus LEG1c/MLP protein has been structurally resolved 38 . Based on the information provided, other LEG1 protein structures from representative vertebrates were predicted using the Phyre2 tool.…”
Section: Structural Prediction Implies That Leg1 Might Retain a Consementioning
confidence: 99%
“…platypus LEG1c/MLP protein has been structurally resolved 38 . Based on the information provided, other LEG1 protein structures from representative vertebrates were predicted using the Phyre2 tool.…”
Section: Structural Prediction Implies That Leg1 Might Retain a Consementioning
confidence: 99%
“…Monotremes express a unique monotreme lactation protein (MLP) in a variety of tissues including milk, with the highest expression occurring in milk cells (Enjapoori et al, 2014). Analysis of the recombinant protein shows it is N-glycosylated, amphipathic and a-helical, and therefore typical of an antimicrobial protein (Enjapoori et al, 2014;Newman et al, 2018). Functional studies have confirmed the recombinant protein has antimicrobial properties against Staphylococcus aureus and a commensal bacteria, Enterococcus faecalis (Enjapoori et al, 2014).…”
Section: Milk Aids Immunological Defense Of the Youngmentioning
confidence: 99%
“…Monotremes express a unique monotreme lactation protein (MLP) in a variety of tissues including milk, with the highest expression occurring in milk cells (Enjapoori et al 2014). Analysis of the recombinant protein shows it is N-glycosylated, amphipathic and -helical, and therefore typical of an antimicrobial protein (Enjapoori et al 2014;Newman et al 2018). Functional studies have confirmed the recombinant protein has antimicrobial properties against Staphylococcus aureus and a commensal bacteria, Enterococcus faecalis (Enjapoori et al 2014).…”
Section: Milk Aids Immunological Defense Of the Youngmentioning
confidence: 99%